RANCANGAN ANTENA RECEIVER AUTOMATIC DEPENDENT SURVEILLANCE BROADCAST (ADSB) FREKUENSI 1090 MHZ MENGGUNAKAN ARDUINO UNO BERBASIS RTL-SDR R820T DAN LOW NOISE AMPLIFIER - Fitriani, Endah; Mandala, Mas Ade (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2023)
With ADS-B technology, it is the aircraft that continuously broadcasts data to the receiver system at the airport. Previously, all airports used radar, which worked the opposite way to the ADS-B technology, namely the radar at the airport which detects airplanes. One of the problems in the development of ADS-B technology is how to monitor and monitor aircraft with equipment technology that can be purchased in Indonesia at low prices, considering that ADS-B equipment in Indonesia is generally purchased abroad at very expensive prices. Therefore, the author will design an ADS-B Receiver Antenna which is designed with an aircraft transponder broadcast frequency of 1090 Mhz and adds a Low Noise Amplifier to reduce noise and maximize the 1090 Mhz frequency reception range. The ADS-B antenna design can receive a reply frequency of 1090 Mhz from the aircraft's transponder and change the received data to then provide information about the aircraft's target using the Virtual Radar application Display on a PC. In addition, this design can also display 1090 MHz Frequency and Antenna Temperature on a 16x2 LCD (light crystal display) using Arduino Uno and IC LM35.